2020
DOI: 10.1155/2020/8887699
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance Observer-Based Nonsingular Terminal Sliding Mode Control for Spacecraft Electromagnetic Docking

Abstract: This paper presents a novel nonlinear sliding mode control scheme that combines on-line model modification, a nonlinear sliding mode controller, and a disturbance observer to solve the essential problems in spacecraft electromagnetic docking control, such as model uncertainties, unknown external disturbances, and inherent strong nonlinearity and coupling. An improved far-field model of electromagnetic force which is much more accurate than the widely used far-field model is proposed to enable the model paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…17 To achieve good orbit-attitude tracking performance an improved finite-time sliding mode control approach is proposed in Shi et al 18 in which the soft docking procedure is separated into three sequential movements with set duration to reduce the complexity, and the high-precision performance of the generated simplified electromagnetic force/torque models is shown by numerical analysis. Another study related to spacecraft docking can be found in Zhang et al 19 in which the essential problems in spacecraft electromagnetic docking control, such as model uncertainties, unknown external disturbances, and inherent strong nonlinearity and coupling, are solved using a nonlinear sliding mode control that combines online model modification, a nonlinear sliding mode controller, and a disturbance observer. In Liu et al, 20 Delayed Electromagnetic Docking of Spacecraft in Elliptical Orbits with Active Disturbance Rejection Control is proposed and validated with a high degree of accuracy however the non-fragile control dealing with controller perturbations is not considered in this study.…”
Section: Introductionmentioning
confidence: 99%
“…17 To achieve good orbit-attitude tracking performance an improved finite-time sliding mode control approach is proposed in Shi et al 18 in which the soft docking procedure is separated into three sequential movements with set duration to reduce the complexity, and the high-precision performance of the generated simplified electromagnetic force/torque models is shown by numerical analysis. Another study related to spacecraft docking can be found in Zhang et al 19 in which the essential problems in spacecraft electromagnetic docking control, such as model uncertainties, unknown external disturbances, and inherent strong nonlinearity and coupling, are solved using a nonlinear sliding mode control that combines online model modification, a nonlinear sliding mode controller, and a disturbance observer. In Liu et al, 20 Delayed Electromagnetic Docking of Spacecraft in Elliptical Orbits with Active Disturbance Rejection Control is proposed and validated with a high degree of accuracy however the non-fragile control dealing with controller perturbations is not considered in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Shi 12 proposed a precious dynamical model of relative motion. Besides, Zhang 13 derived a 9-DOF dynamics for spacecraft electromagnetic docking. After referring to the works, considering the nonlinear dynamics of the multibody spacecraft and uncertain unbalance of large-size payload, a more accurate 9-DOF dynamics are put forward in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Considering the nonlinearity of the AMB system, coupled multibody dynamics, and the imbalance of large but uncertain payload, a high-precision control method of multibody spacecraft is derived after dynamical model proposed. Some nonlinear control methods have been studied in the literature for the nonlinear and coupled system, such as robust control, 17,18 sliding mode control, 19,13 backstepping control, [20][21][22][23][24] and iterative learning control. 25,26 These methods are investigated for attitude and AMB system control.…”
Section: Introductionmentioning
confidence: 99%